Role of Cytokines in Thymus- Versus Peripherally Derived-Regulatory T Cell Differentiation and Function - Goldstein, jérémie d.; Pérol, Louis; zaragoza, bruno; baeyens, audrey; marodon, gilles; Piaggio, Eliane (Frontiers in Immunology, 2013)
CD4+CD25+Foxp3+ regulatory T cells (Tregs) are essential players in the control of immune responses. Recently, accordingly to their origin, two main subsets of Tregs have been described: thymus-derived Tregs (tTregs) and peripherally derived Tregs (pTregs). Numerous signaling pathways including the IL-2/STAT5 or the TGF-β/Smad3 pathways play a crucial role in segregating the two lineages. Here, we review some of the information existing on the distinct requirements of IL-2, TGF-β and TNF-α three major cytokines involved in tTreg and pTreg generation, homeostasis and function. Today it is clear that signaling via the IL-2Rβ chain (CD122) common to IL-2 and IL-15 is required for proper differentiation of tTregs and for tTreg and pTreg survival in the periphery. This notion has led to the development of promising therapeutic strategies based on low-dose IL-2 administration to boost the patients' own Treg compartment and dampen autoimmunity and inflammation. Also, solid evidence points to TGF-β as the master regulator of pTreg differentiation and homeostasis. However, therapeutic administration of TGF-β is difficult to implement due to toxicity and safety issues. Knowledge on the role of TNF-α on the biology of Tregs is fragmentary and inconsistent between mice and humans. Moreover, emerging results from the clinical use of TNF-α inhibitors indicate that part of their anti-inflammatory effect may be dependent on their action on Tregs. Given the profusion of clinical trials testing cytokine administration or blocking to modulate inflammatory diseases, a better knowledge of the effects of cytokines on tTregs and pTregs biology is necessary to improve the efficiency of these immunotherapies.